2014
DOI: 10.1007/s11105-014-0829-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a T-DNA Promoter Trap Line of Arabidopsis thaliana Uncovers an Embryo Sac-Specific Bi-directional Promoter

Abstract: The Arabidopsis thaliana promoter trap line showing uidA reporter gene expression specifically in mature embryo sacs was found to carry transfer DNA (T-DNA) insertion in the 5′ untranslated region (UTR) of At3g17150. At3g17140 and At3g17150 are a pair of head-tohead-oriented genes separated by a 668-bp intergenic region encoding for a putative pectin methyl esterase inhibitor protein. In the GUS-650 line, uidA reporter gene was inserted in head-to-head orientation to the At3g17140 gene. Presence of At3g17140 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The T-DNA insertion site was determined through the genome walking approach (Pratibha et al, 2013;Sharma et al, 2015). Briefly, genome walking libraries were constructed by digesting DNA with DraI, EcoRV, PvuII, or StuI restriction enzyme followed by adapter ligation.…”
Section: Identification and Confirmation Of The T-dna Insertion Sitementioning
confidence: 99%
“…The T-DNA insertion site was determined through the genome walking approach (Pratibha et al, 2013;Sharma et al, 2015). Briefly, genome walking libraries were constructed by digesting DNA with DraI, EcoRV, PvuII, or StuI restriction enzyme followed by adapter ligation.…”
Section: Identification and Confirmation Of The T-dna Insertion Sitementioning
confidence: 99%
“…An Arabidopsis thaliana mutant showing high seed sterility was identified in a T-DNA promoter trap mutant population. This line, designated as GUS-650, carries a promoter-less uidA reporter gene and showed GUS expression in the ovules (for details see Sharma et al 2015). Further, the T-DNA was found to be inserted in the 5′ UTR of At3g17150 gene coding for P ectin M ethyl E sterase Inhibitor ( PMEI ) and was specifically expressing in the mature embryo sacs.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the roles of embryo sac cellularization and cell wall composition in differentiation of gamete specification have not been investigated so far. Investigation of an Arabidopsis thaliana T-DNA promoter trap mutant showing GUS expression in the embryo sac (Sharma et al, 2015) revealed mis-specification of gamete cells leading to high seed sterility. Here we report that the loss-of-function mutation in the At3g17150 gene annotated to code for a “pectin methylesterase inhibitor” results in this shift in cell fate thereby revealing the role of cell-wall in determining cell fate of female gametophyte and subsequent embryo development.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of natural bidirectional promoters have focused on the model plant Arabidopsis. Examples of bidirectional promoters identified in Arabidopsis include two gene pairs, cab1/cab2 and At5g06290/At5g06280 , involved in photosynthesis which have 2177- and 351-bp bidirectional promoters, respectively ( Bondino and Valle, 2009 ; Mitra et al , 2009 ); 668- and 461-bp intergenic regions in the At3g17140/At3g17150 and At4g10596/At4g110600 gene pairs identified by characterization of two T-DNA promoter trap lines ( Pratibha et al , 2013 ; Sharma et al , 2014 ); an asymmetric bidirectional promoter in the At1g71850 / At1g71860 gene pair ( Liu et al , 2015 ); and a heat-inducible bidirectional promoter in the AtClpB-C / AtCK2 gene pair ( Mishra and Grover, 2014 ).…”
Section: Introductionmentioning
confidence: 99%